Effect of histone acetylation on structure and in vitro transcription of chromatin. - Mathis, D J (1978)
n-Butyrate treatment of growing Hela cells produces a dramatic increase in the levels of histone acetylation. We have exploited this system to study the effect of histone acetylation on chromatin structure. Chromatin containing highly acetylated histones is more rapidly digested to acid-soluble material by DNase I, but not by micrococcal nuclease. The same pattern of nuclease sensitivity was exhibited by in vitro-assembled chromatin consisting of SV40 DNA Form I and the 2 M salt-extracted core histones from butyrate-treated cells. Using this very defined system, it was possible to demonstrate that acetylated nucleosomes do not have a greatly diminished stability. Stability was measured in terms of exhange of histone cores onto competing naked DNA or sliding of histone cores along ligated naked DNA. Finally, it was shown that acetylated nucleosomes are efficient inhibitors of in vitro RNA synthesis by the E. coli holoenzyme as well as by the mammalian polymerases A and B.